The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s1516-635x2007000300003
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the compound chlorpyrifos+ cypermethrin+citronellal against Alphitobius diaperinus: laboratory analysis and residue determination in carcasses

Abstract: Effectiveness, biological security and the absence of residues in meat and/or eggs must be considered when recommending options for the control Alphitobius diaperinus in poultry production environments. This research study evaluated the effectiveness of cypermethrin+ chlorpyrifos+citronellal in the control of A. diaperinus, including analysis for the presence of residues of this compound in poultry carcasses (experimental farm). Two studies were carried out under laboratory conditions. One used paper filters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
2
0
3
Order By: Relevance
“…Currently, the insecticides registered for application in poultry facilities in Brazil include pyrethroids and organophosphates that contain the active ingredients cypermethrin and chlorpyrifos, respectively. These insecticides are widely used, isolated or in mixture, in commercial formulated products against A. diaperinus (Silva et al 2007, Oliveira et al 2016. This reduced number of insecticides registered for use against this species favors the evolution of resistance.…”
mentioning
confidence: 99%
“…Currently, the insecticides registered for application in poultry facilities in Brazil include pyrethroids and organophosphates that contain the active ingredients cypermethrin and chlorpyrifos, respectively. These insecticides are widely used, isolated or in mixture, in commercial formulated products against A. diaperinus (Silva et al 2007, Oliveira et al 2016. This reduced number of insecticides registered for use against this species favors the evolution of resistance.…”
mentioning
confidence: 99%
“…Although SILVA et al (2007) observed 100% of effectiveness rate for chlorpyrifos, cypermethrin, and citronellal insecticide in the laboratory against A. diaperinus larvae and adults, to obtain 100% of effectiveness rate in field routine is not so simple due to the complexity of controlling A. diaperinus (CHERNAKI-LEFFER et al 2007, WOLF et al 2015. Only the use of chemical products is not enough to control the insect infestation, and the answer could be variable, heavily depending on environmental characteristics of the house (CHERNAKI-LEFFER et al 2007).…”
Section: Palavras-chavementioning
confidence: 99%
“…O controle do Alphitobius diaperinus em ambientes avícolas tem sido realizado com a finalidade de reduzir a população dos besouros, com menor custo, menor risco e maior eficiência (SILVA et al, 2007, VITTORI et al, 2007, MARCOMINI, et al, 2009, WOLF et al, 2015, DEL VALLE et al, 2016. Uma vez estabelecidos nas instalações, tais coleópteros, conhecidos como "cascudinhos", multiplicam-se rapidamente, sendo encontradas elevadas populações em cama de frangos de corte, de matrizes, e em fezes de poedeiras confinadas em gaiolas (ARENA et al, 2020).…”
Section: Introducãounclassified
“…O A. diaperinus tornou-se uma das principais pragas avícolas (SILVA et al, 2007;SOUZA et al, 2009;CHARLIE-SILVA et al, 2019) de grande preocupação sanitária devido os vários prejuízos que podem ocasionar. Podem ser reservatórios de patógenos como Clostridium perfringens, Campilobacter spp., Escherichia, Salmonella e vírus causadores das doenças de Marek, Gumboro e Newcastle (SAFRIT; AXTELL, 1984;BATES et al, 2004;SEGABINAZI et al, 2005;VITTORI et al, 2007;GEHRING et al, 2020).…”
Section: Introducãounclassified